2014
DOI: 10.5090/kjtcs.2014.47.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma Dorsi: Clinicopathological Analysis of 76 Cases

Abstract: BackgroundWe aimed to investigate the epidemiological, clinical, paraclinical, and treatment aspects of elastofibroma dorsi through a retrospective study of 76 patients who underwent surgery between January 2008 and December 2012 in our department.MethodsOur study is retrospective between January 2008 and December 2012. We admitted 79 patients with a subscapular mass, and only 76 patients had ED. The others (n=2) had high associated risk of anesthesia and were managed by a medical treatment and one patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 20 publications
6
30
1
Order By: Relevance
“…Despite the fact that few cases related to this pathology were reached in the literature reviews, Brandser et al have reported this rate to be 2% in their studies of thoracic CT in asymptomatic elderly populations [2]. It is usually seen in the population over 55 years of age, however, there are some cases that are detected at younger ages [3,4]. It was reported that it is seen 8-13 times more among women than in men [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that few cases related to this pathology were reached in the literature reviews, Brandser et al have reported this rate to be 2% in their studies of thoracic CT in asymptomatic elderly populations [2]. It is usually seen in the population over 55 years of age, however, there are some cases that are detected at younger ages [3,4]. It was reported that it is seen 8-13 times more among women than in men [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of bilateral occurrence of elastofibroma dorsi, which is usually observed unilaterally, is 10%. It is thought that bilateral cases are often synchronous [4,10]. More than 80% of elastofibroma dorsi are localized in the subscapular region, which is between the rhomboid and latissimus dorsi muscles and the sixth and eighth ribs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoechoic tissue strands represent fat, and the hyperechoic tissue strands represent fibroelastic tissue. No significant flow is found on color Doppler imaging . Further investigation on CT or MRI is usually needed to delineate the full extent of the lesion, owing to its obscuration by the scapula (Figure B).…”
Section: Chest‐wall Pathologymentioning
confidence: 99%
“…No significant flow is found on color Doppler imaging. [28][29][30][31][32][33] Further investigation on CT or MRI is usually needed to delineate the full extent of the lesion, owing to its obscuration by the scapula (Figure 22B).…”
Section: Tumormentioning
confidence: 99%